Hubungan Perilaku Merokok Dengan Kejadian Infeksi Saluran Pernafasan Akut (ISPA) Pada Balita Di Wilayah Kerja Puskesmas Plaju Kota Palembang - Nabil, M; Januar, Rico; Ernia, Rima; Viranada, Dina Renada (JURNAL KESEHATAN TERAPAN, 2024)
Acute Respiratory Tract Infection is a disease of the upper and lower respiratory tract which can usually be contagious and can even cause death, this depends on environmental factors and host factors. The aim of the research was to determine smoking behavior factors related to the incidence of ISPA in toddlers in the work area of the Plaju Health Center, Palembang City. This type of research uses a quantitative analytical method using a cross sectional approach. The population in this study were all mothers who had toddlers aged 1-5 years, namely 253 toddlers. Sampling used accident sampling of 80 respondents. Statistical analysis uses the Chi Square test with questionnaires and interviews. Based on the research results, it shows that there is a relationship between family members' smoking behavior (p= 0.004), use of mosquito coils (p= 0.001), humidity (p= 0.011), lighting (p= 0.008) and house ventilation (p= 0.007) with the incidence of ARI. in toddlers. It is hoped that Puskesmas officers will increase their role in providing education to the community so that they can avoid smoking behavior, especially among parents who have toddlers, so that the incidence of ISPA can be reduced